(untitled) (Innovate Conferences, 2025)
This article delves into the innovative poetic structures and resonant themes found in the narrative styles of Mikhail Lermontov and Alexander Pushkin, two titans of 19th-century Russian literature. While both authors draw from the Romantic tradition, their unique approaches to form and content reveal distinct avenues for exploring the complexities of the human experience. An analysis of their respective works highlights how Lermontov’s rhythmic experimentation contrasts with Pushkin’s elegant simplicity, even as both writers grapple with themes of love, identity, nature, and society. This exploration underscores the impact of structure and thematic depth on the reader’s engagement, illuminating the significance of both authors within the literary canon.